Learning from the Carbon Fiber-Reinforced Plastic Project - Mohamed, Prof. Ts. Dr. Saiful Bahri; Ab Rashid, Prof. Madya Dr. Radzuwan; Muhamad @ Mohd Saufi, Ts. Dr. Martini (Springer Verlag, 2019)
Design-Expert V9 software was used to predict the cutting parameters that had an important effect for a particular response. Since the surface roughness for CFRP and Al2024 was recorded as two different responses, the analysis was conducted separately. The obtained results from the experiment are listed in Table 4.1 which is then used for further analysis using Design-Expert V9 software. The input variables were spindle speed, feed rate, and depth of cut; meanwhile, the responses were surface roughness for CFRP and Al2024. The analysis began with the analysis of CFRP machined surface and then followed by Al2024 machined surface.